RESILIENT FILE SYSTEM - Галата, Л. П.; Максимов, Ю. О. (Science-based technologies, 2014)
This article analyzes the implementation of disk structure Resilient File System, a new structural elements – «B +- trees», their influence on scaling elements of filesystem. Explored the advantages and disadvantages of architecture, performance and fault tolerance, compared with the New Technology File System. The estimation of efficiency of recovering files after a hardware failure occurs on the basis of metadata structures that can detect all forms of disk damage and of strategies «Copy-on-Write ( copy -on- account )". Transaction logs are considered as an approach to maintain consistency on the disk and reliability in the disk drive upgrades. Used approach "placement while recording " for maximum reliability and prevent dangling entries. Tested checking redundancy data storage system and the speed of the search attribute in the example folder. Investigated integral streams that protect file content from all kinds of data damage. Listed technology to increase the security of the file system.